Balancing the sustainability in the 2030 agenda: the OECD countries. - García-Peña, María del Carmen; Díaz-Díez, Bárbara; Muñoz-Martos, María del Mar (Taylor & Francis, 2022)
When assessing the achievement of the 2030 Agenda, the equili-brium among the dimensions of the sustainable development shouldbe taken into account, recognizing the balanced and integratednature of the Sustainable Development Goals (SDGs). To this end,we propose the use of a Balance Index to complement the perfor-mance indexes of the SDGs and the integration of sustainable devel-opment dimensions and experts’ opinions in the normalizationprocess. The data source is the 2020 SDG Index Report proposed bythe Bertelsmann Stiftung and the Sustainable DevelopmentSolutions Network. Provide and analyse the performance and thebalance indexes for OECD countries. Finally, we propose a visualmatrix of the two indexes with four progress scenarios to orientatethe decision-making. This proposal allows a more accurate quantifi-cation of the situation of each country and is, therefore, a useful toolfor evaluating the integrated nature of the sustainability (SDG 17).
Keywords: Desarrollo sostenible - Países de la Organización de Cooperación y Desarrollo Económico; 2030 agenda; Balance; Sustainable development; Policy integration; Sustainable development goals; Concentration index; Composite indicators